An illustration of logistic regression technique: a case of processed food sector. (1st January 2014) - Mahajan, Rajneesh; Garg, Suresh; Sharma, P.B.
The effectiveness of logistic regression had been understood by many authors. A special attention is paid by authors to write section on multivariate statistics in books. The books have explained the theoretical method of predicting the dichotomous dependent variable from a set of binary explanatory variables and their relationship is not linear but interacts with each other. The logistic regression is free from various restrictive assumptions as required in case of ordinary regression or least square regression. The objective of the current research paper is to illustrate how effective is the logistic regression applied in processed food supply chain management. A primary survey was conducted and 252 responses were gathered to conduct the research. A complete step by step process of logistic regression is explained in the current paper. The results of paper confirm that logistic regression is an effective tool for research and it can be applied to various other sectors such as human resource management, etc.